Dukungan Keluarga pada Anak Retardasi Mental: Literatur Review - Inda Eva; Prita Adisty Handayani; Elis Hartati (Indonesian Journal of Nursing Research (IJNR), 2021)
Mentally retarded children are those with below average intelligence since developmental years and have deficits in their social skills. This study used a literature review design. The inclusion criteria in this study were articles with the last 5 years of publication and full text was available. The samples in this study were children with mental retardation, deaf children, autistic children, and children with attention deficit hyperactivity disorder (ADHD). The data collection instruments used included a family support questionnaire, a self-concept questionnaire, a community support questionnaire, a quality of life questionnaire, a social skills questionnaire, and an observation sheet. The search was carried out using Googel Scholar, Ebscohost, Proquest and then obtained 10 articles that met the criteria. The article reviewed has four family supports namely: emotional support, appraisal, appreciation, and instrumental. The results of the literature review found that family support has a positive impact on children with mental retardation, such as helping to independent children in doing oral hygiene, helping children to increase energy intake, improving children's social skills, increasing self-care independence, and improving children's quality of life. Families, especially parents, are expected to be able to maximize the four family supports for children with mental retardation.